PENGARUH PASANG SURUT DISALURAN PADA KAWASAN PERSAWAHAN - Martini, RA Sri; Revisda, Revisda; Kharisma, Riri (Jurnal Teknik Sipil, 2023)
Tides are a natural phenomenon of periodic rise and fall of water levels caused by gravitational forces and the force of attraction. This can naturally increase water levels and floods which are usually called tidal floods.To overcome this, drainage was created to reduce overflow at high tide and add water at low tide.The Lalan Sub-Watershed, Lalan District, Musi Banyuasin Regency is one of the sub-watersheds of the Musi Watershed which is influenced by tides. The average height of secondary channels in the Lalan sub-basin is 1.15 m with an average flow discharge of 528.96 m3/sec. The highest tidal water level is 1.21 m with a flow discharge of 978.79 m3/s while the lowest low tide water level is 0.33 m with a flow discharge of 234.95 m3/s. This causes water to overflow at the highest tide, thereby submerging the rice fields that are irrigated by the sub-basin and experiencing drought at low tide. To overcome this, a sluice gate is needed in the secondary channel to regulate the entry and exit of water.